Migration and shifting borders: Re-conceptualizing non-citizens in Turkey - Holle, Jessica Zerrin (AUC Knowledge Fountain, 2018)
In an age of securitization, in which the movement of individuals across borders has become securitized, and in which borders themselves are being externalized in an attempt to curb migration flows, the conventional notion of a static citizen-state relationship within the nation-state system is increasingly becoming inapplicable. Central to this thesis is the question: In a climate of securitized migration, and against the backdrop of the refugee/migration "crisis" has the externalization of EU borders through its migration management partnership with Turkey contributed to or brought about alternative conceptualizations of foreignness, citizenship, and non-citizenship in Turkey? Protection for asylum seekers in Turkey, and increasingly in other countries, is governed by the understanding that the presence of non-citizens and non-nationals will be temporary. By focusing on Turkey, and the recent shifts in its legal landscape on foreigners, it is possible to examine how different conceptions of citizenship and membership could be theorized against the backdrop of both the securitization of migration and the externalization of EU borders through the proliferation of the non-entrance and containment policies central to its migration management. In order to understand more tangibly the impact of securitization and externalization, focusing on a particular country is necessary as the implications these ongoing processes become clearer. The thesis examines how borders shift and how non-citizens are conceptualized in Turkey, while considering the post-2001 global context. It argues that the recent formalization on how foreigners are legally governed in Turkey is connected to EU migration management, and more broadly, to the growing trend of non-entrance regimes and containment policies. Turkey's recent shifting legal landscape on foreigners and protection is a platform to examine how alternative theoretical conceptions of citizenship might emerge in Turkey.